A Mixed-Methods Analysis of Gender and Career Status Differences in the Impact of the COVID-19 Pandemic on Underrepresented Postdoctoral Fellows and Early-Career Faculty - White, Gretchen E; Proulx, Chelsea N; Morone, Natalia E; Thakar, Maya S; Murrell, Audrey J; Althouse, Andrew D; Rubio, Doris M (Academic medicine, 2022)
The lack of racial and ethnic diversity in the biomedical workforce is pronounced and those from underrepresented backgrounds encounter more challenges than their majority counterparts. The extent of the impact of the COVID-19 pandemic on early-career investigators from underrepresented backgrounds is not yet fully understood. To examine the impact of the pandemic on underrepresented early-career biomedical researchers, this study evaluated differences in productivity, research, and psychological well-being by gender and career status. This was a cross-sectional analysis of preintervention data, collected in September-October 2020, from 220 participants enrolled in the Building Up a Diverse Biomedical Research Workforce study. Participants were from 25 academic medical centers in the United States and were underrepresented early-career researchers. The primary outcomes were agreement on a 5-point Likert scale with pandemic impact statements (e.g., "The COVID-19 pandemic has impacted my ability to conduct research"). Thematic analysis was conducted on responses to 2 open-ended questions assessing the pandemic's impact. Most participants were female (79.9%), of non-Hispanic/Latinx/Spanish origin Black/African American (33.2%) or Hispanic/Latinx/Spanish origin (34.1%), and early-career faculty (53.4%). Over half of participants agreed or strongly agreed that the COVID-19 pandemic impacted their ability to work (55.7%) and conduct research (70.7%). Themes from qualitative analysis suggested lower research productivity, concerns about the academic job market and funding, and psychological distress due to the pandemic. Women were more likely to attribute lost productivity and psychological distress to homeschooling and childcare responsibilities. Postdoctoral fellows were concerned about more competition for fewer academic positions. In this study of early-career underrepresented biomedical researchers, the impact of the COVID-19 pandemic was widely felt by participants, varying by gender and career status. For those postdoctoral fellows and early-career faculty who are underrepresented, it is critical for institutions to offer flexibility in their positions.